2015
DOI: 10.1007/s10811-015-0671-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seaweed extract (Ulva rigida) on the water deficit tolerance of Salvia officinalis L

Abstract: The present investigation examined the effect of a seaweed extract (SWE) of Ulva rigida applied at different concentrations: 25, 50, and 75 % to sage plant (Salvia officinalis L.) subjected to drought stress tolerance. Three watering treatments, without stress (WS), moderate water deficit (MWS), and severe water deficit (SWD) corresponding respectively to 82, 18, and 7 % field capacity (FC), were used to understand the metabolic and physiological changes of Salvia plant during water deficit. SWE application en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…On the one hand, seaweed extracts are among the most common substances used as biostimulants and they might play a role in counteracting drought stress [35]. Indeed, Ascophyllum nodosum extracts have been shown to enhance drought tolerance in tomato [36], soybean [37], bean [38], and Salvia officinalis [39], by modulating the osmotic and antioxidant response to…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, seaweed extracts are among the most common substances used as biostimulants and they might play a role in counteracting drought stress [35]. Indeed, Ascophyllum nodosum extracts have been shown to enhance drought tolerance in tomato [36], soybean [37], bean [38], and Salvia officinalis [39], by modulating the osmotic and antioxidant response to…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, seaweed extracts are among the most common substances used as biostimulants and they might play a role in counteracting drought stress [35]. Indeed, Ascophyllum nodosum extracts have been shown to enhance drought tolerance in tomato [36], soybean [37], bean [38], and Salvia officinalis [39], by modulating the osmotic and antioxidant response to stress. On the other hand, yeast extracts are substances known to increase the yield and quality of different crops, including tomato [40], orange [41] and wheat [42], under both control and stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in chlorophyll content can be explained by the bioactive components found in U. lactuca extracts, such as ascorbic acid, betaine, glutathione and proline, which would actively participate in the alleviation during stress periods of plants (Ibrahim et al, 2014). A study conducted by Mansori et al (2015) showed that plants of sage (Salvia officinalis L.) under water stress conditions showed increased glycine betaine levels, but these decreased significantly when extracts of Ulva rigida C. Agardh at 50% were applied. Glycine betaine is abundant mainly in chloroplasts where it participates in the adjustment and protection of the thylakoid membrane, and also helps stabilize the quaternary structures of complex proteins in the photosystem II, thereby maintaining photosynthetic efficiency (Genard et al, 1991;Papageorgiou and Murata, 1995).…”
Section: Production Parameters In Lettuce With the Use Of Pellets Andmentioning
confidence: 99%
“…Acidic Ulva extracts were used to replace synthetic antioxidants and to protect different cosmetic products from oxidation [39]. Ulva aqueous extracts were used for the synthesis of gold and silver nanoparticles, with excellent biocompatibility on healthy cells and were highly cytotoxic against colorectal cancer cell lines HT-29 and Caco-2 [40]. A new food-grade protein extraction protocol was proposed from Ulva and showed high digestibility in simulated gastro-intestinal tests with a high antioxidant activity [27].…”
Section: Potential Riches Of Ulvamentioning
confidence: 99%
“…Water extraction of sulphated ulvan gives a product with a high antimicrobial activity against Enterobacter cloace and Escherichia coli [63]. A simple acidic method for extraction of Ulvan, with relatively low content of protein and high sulphate, is frequently used [30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64]. The properties and bioactivities of polysaccharides can be modulated by the extraction conditions; where rhamnose, glucuronic acid and glucose are the major monosaccharides obtained at 90 °C with 0.01 M HCl.…”
Section: Processes and Strategies To Extract Component From Ulvamentioning
confidence: 99%